Pengaruh Ukuran Perusahaan, Harga Saham dan Return On Asset Terhadap Price to Book Value pada Perusahaan Pertambangan yang Terdaftar Di Bursa Efek Indonesia Priode 2020-2024 - Isma Isalahul Mustaqim (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
This study aims to analyze the effect of Firm Size (FIRMSIZE), Return On Asset (ROA), and Stock Price (SAHAM) on Price Book Value (PBV) in mining companies listed on the Indonesia Stock Exchange (IDX) for the period 2020–2024. The method used is panel regression with a random effects approach. The results show that, partially, Company Size has a significant negative effect on PBV, ROA has no significant effect, and Stock Price has a significant positive effect on PBV. Simultaneously, all three variables have a significant effect on PBV with a calculated F-value > F-table and a probability < 0.05. The coefficient of determination (R-squared) of 0.373670 indicates that 37.3670% of PBV variation can be explained by FIRMSIZE, ROA, and STOCK, while the remaining 62.6330% is influenced by other factors not examined in this study. The results of this study are expected to serve as a reference for investors and company management in understanding the factors that influence company valuation in the capital market.